2007
DOI: 10.2459/01.jcm.0000260822.29843.c9
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous ST-segment elevation in the right precordial and inferior leads in Brugada syndrome

Abstract: We report the case of a patient with genetically confirmed Brugada syndrome who presented with ST-segment elevation in the right precordial and inferior leads. The presenting arrhythmia was atrial fibrillation, which degenerated into ventricular fibrillation during intravenous amiodarone. A flecainide test was markedly positive. Four appropriate cardioverter-defibrillator discharges occurred during a two-year follow-up period after implantation of the device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…The diagnosis of BrS was established after documentation on 12-lead ECG of a spontaneous coved Brugada pattern in the inferior leads and a flecainide-induced coved Brugada pattern in the right-sided precordial leads. As previously reported for this patient, 3 genetic testing was positive for a nonsense SCN5A mutation (R179X), which has been found to be associated with a Brugada ECG pattern in the inferior/right precordial leads and produces a nonfunctional cardiac sodium channel, carrying a more severe arrhythmic phenotype. 4 Accordingly, despite antiarrhythmic therapy with quinidine, our patient experienced recurrent appropriate ICD interventions (until February 2013, 11 isolated ICD shocks and 1 arrhythmic storm).…”
Section: Case Reportsupporting
confidence: 77%
“…The diagnosis of BrS was established after documentation on 12-lead ECG of a spontaneous coved Brugada pattern in the inferior leads and a flecainide-induced coved Brugada pattern in the right-sided precordial leads. As previously reported for this patient, 3 genetic testing was positive for a nonsense SCN5A mutation (R179X), which has been found to be associated with a Brugada ECG pattern in the inferior/right precordial leads and produces a nonfunctional cardiac sodium channel, carrying a more severe arrhythmic phenotype. 4 Accordingly, despite antiarrhythmic therapy with quinidine, our patient experienced recurrent appropriate ICD interventions (until February 2013, 11 isolated ICD shocks and 1 arrhythmic storm).…”
Section: Case Reportsupporting
confidence: 77%
“…reported associated Type 1 ST elevation (in addition to anterior precordial leads) in either aVR,V6 or inferior leads in upto 10% of patients with BS [21]. Occasional cases of Brugada-type ST elevation in isolated inferior and lateral precordial leads have also been reported [22], [23], [24], [25], [26], [27], [28]. While the exact mechanism of this finding has not been elicited, a novel mutation in sodium channel gene was suggested in one of the reports [26].…”
Section: Discussionmentioning
confidence: 98%
“…1 However, sporadic cases have been reported in which the "coved-type" Brugada ECG pattern was also observed in the inferior or lateral ECG leads. [2][3][4][5] Sarkozy et al reported in a large cohort of patients with BrS (280 patients) that the "coved" Brugada pattern did not occur spontaneously in the inferior or lateral leads but rather after challenging with sodium blockers. 6 These data suggest that the presence of spontaneous "coved" ST elevation in the inferior-lateral leads is an exceptional finding in BrS.…”
Section: Discussionmentioning
confidence: 99%